Collaboration Strategy with Stakeholders Through the Implementation of Electrifying Marine to Increase Sales Growth - Maria, Yulita (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The geographical condition of East Kalimantan Province, especially Berau Regency, is a tourist area with islands and coastal areas where water transportation is a fundamental need for the community to reach various isolated areas. It is known that the water transportation equipment used still uses diesel engines, so there is a potential for captive power acquisition when the ship docks at the port by switching to PLN services. Under the condition of a power surplus, it is expected that electricity sales will increase in 2022, especially at the L tariff through a breakthrough program in seeking potentials that can increase electricity sales. This study uses a qualitative method. In setting the Key Performance Indicator (KPI) for 2022, electricity sales growth is targeted at 269.3 GWh, but sales growth at the L rate is still low. Therefore, it must be achieved by acquiring captive power of ships at berthing ports and connecting PJU Mandiri around the port. The potential L tariff customer segment is a priority in the marketing strategy and increasing electricity sales.